2018
DOI: 10.1002/btm2.10104
|View full text |Cite
|
Sign up to set email alerts
|

Rescuing mesenchymal stem cell regenerative properties on hydrogel substrates post serial expansion

Abstract: The use of human mesenchymal stem/stromal cells (hMSCs) in most clinical trials requires millions of cells/kg, necessitating ex vivo expansion typically on stiff substrates (tissue culture polystyrene [TCPS]), which induces osteogenesis and replicative senescence. Here, we quantified how serial expansion on TCPS influences proliferation, expression of hMSC‐specific surface markers, mechanosensing, and secretome. Results show decreased proliferation and surface marker expression after five passages (P5) and dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 48 publications
1
42
0
Order By: Relevance
“…This mechanical desensitization has also been seen in MSCs from older donors, where YAP nuclear translocation is decreased and RUNX2 expression is down-regulated on stiff gels compared to young MSCs (46,47). Even with passaging, this dysregulation has been observed (6). Furthermore, the blocked nuclear mechanosensing might have induced a feedback loop to the cytoplasm; a possible reason why we observed a decrease in cell spreading with stiffening compared to the mCherry control (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 61%
“…This mechanical desensitization has also been seen in MSCs from older donors, where YAP nuclear translocation is decreased and RUNX2 expression is down-regulated on stiff gels compared to young MSCs (46,47). Even with passaging, this dysregulation has been observed (6). Furthermore, the blocked nuclear mechanosensing might have induced a feedback loop to the cytoplasm; a possible reason why we observed a decrease in cell spreading with stiffening compared to the mCherry control (SI Appendix, Fig.…”
Section: Discussionsupporting
confidence: 61%
“…Several biomaterial strategies have been explored to maintain more homogeneous MSCs during the expansion phase of MSC manufacturing. For example, Rao et al (41) showed that expanding hMSCs on soft poly(ethylene glycol) hydrogel matrices was able to avoid reductions in cell surface marker expression and cytokine expression that was observed when hMSCs were serially passaged on polystyrene. Growing MSCs in three-dimensional (3D) culturing systems has also been beneficial in maintaining early-passage MSC phenotype during expansion (42,43).…”
Section: Impact Of Sourcing and Manufacturing/storage On The Functionmentioning
confidence: 99%
“…Due to this high water content, hydrogels exhibit favorable biocompatibility and as such have been developed for and used in a variety of medical applications 1‐3 . Since hydrogel properties can be tuned through a variety of chemical approaches, their rational design and engineering has enabled new modalities for delivery of small molecules, 4‐7 proteins, 8‐12 and cells 13,14 and as tissue engineering scaffolds for directing cell fate/lineage, 15,16 stem cell expansion, 17‐20 and tissue regeneration 21‐25 . Research efforts to develop hydrogels for biomedical applications represents one of the most studied areas at the interface of engineering and medicine 26 .…”
Section: Introductionmentioning
confidence: 99%